L'ombudsman: première avenue de contrôle de l'Administration, ses caractéristiques, son efficacité - Garant, Patrice; Pagé, Huguette (Les Cahiers de droit, 1982)
The Ombudsman is one of the three recognised control agents of today's Public Administration. He has his own characteristics that make him the most accessible, speedy, low cost and efficient instrument of safeguard against illegal, irregular or arbitrary administrative action. A thorough study of the Ombudsmen of two major provinces, Ontario and Québec, is more than interesting and makes one wonder why the 1978 federal project was abandonned. In a broad perpective, that includes a cost-benefit analysis, a comparison between the Ombudsman and the system of administrative appeal or review tribunals allows us to characterize each's specific role and evaluate the need they are respectively intended to fill.